Comorbidities and menopause assessment in women living with HIV - Caixas, Umbelina (2024)
Women living with HIV are reaching older age and experiencing menopause and age-related comorbidities. Data suggest that women living with HIV experience earlier menopause and more menopausal symptoms and age-related comorbidities compared to women without HIV. However, there are no guidelines on the screening for and management of age-related comorbidities and events in women living with HIV. Moreover, little is known about provision of care to this population across Europe. We surveyed 121 HIV healthcare providers in 25 World Health Organization European countries to ascertain screening practices for, and management of, menopause, psychosocial and sexual well-being and age-related comorbidities in women with HIV. Most respondents screened for diabetes, cardiovascular disease (CVD) risk factors and poor mental health at least annually. Low bone mineral density (BMD) was regularly checked but less than once a year. Fewer regularly screened for sexual well-being and intimate partner violence. Menstrual pattern and menopausal symptoms in women aged 45–54 were assessed by 67% and 59% of respondents. 44% stated that they were not confident assessing menopausal status and/or symptoms. CVD, diabetes, low BMD and poor mental health were managed mainly within HIV clinics, whereas menopause care was mainly provided by gynaecology or primary care. Most respondents stated a need for HIV and menopause guidelines. In conclusion, we found that whilst metabolic risk factors and poor mental health are regularly screened for, psychosocial and sexual well-being and menopausal symptoms could be improved. This highlights the need for international recommendations and clinician training to ensure the health of this population.